Development Analysis of Insurance Markets in the EEU - SERIKOVA, Gulzira; SEMBEKOV, Amir; OMAROVA, Ainura; KUZGIBEKOVA, Svetlana; TINGISHEVA, Ainur; BUDESHOV, Eraly (Journal of Advanced Research in Law and Economics; Vol 8 No 4(26) (2017): JARLE Volume 8 Issue 4(26) Summer 2017, 2017)
The analysis of insurance markets in the EEU countries presupposes, first of all, an assessment of the level of development of the insurance market in each of the EEU countries in order to identify common features and differences. The results of the analysis will allow us to outline possible directions for its further improvement. Analyzing the current state of development of Kazakhstan's insurance market, in general, one can say about the trends of positive development. The modern insurance market in Kazakhstan is characterized by an increase in the volume of insurance operations, the emergence of new areas of insurance activity, the exacerbation of competition and increased attention of foreign insurers to the situation with insurance business in Kazakhstan.